Reliability Improvement of Defense Scheme Implementation Using Adaptive Load Shedding Based On System Strength Index - Widyantara, Dwitiya Bagus; Garniwa, Iwa; Jufri, Fauzan Hanif (Universitas Indonesia, 2025)
One of the defense schemes in power systems is Under Frequency Load Shedding (UFLS), designed to mitigate cascading blackouts caused by frequency disturbances. UFLS operates based on predetermined frequency thresholds and time delays, which inherently characterizes it as a static protection mechanism and may cause unnecessary excessive or insufficient load shedding. Therefore, an Adaptive Load Shedding (ALS) approach started to gain popularity, which enables load shedding based on real-time conditions, particularly during generator outages. In this research, a comparative analysis is conducted between the conventional UFLS method and a newly developed ALS scheme that integrates the System Strength Index (SSI) to improve the system's reliability, as evaluated by Energy Not Served (ENS). The proposed ALS algorithm processes real-time feeder load data, ranks the feeders by load magnitude in descending order, and optimizes the load shedding setpoints by incorporating the SSI. The proposed method is simulated in the Flores power system model using actual historical data for two load conditions: the highest and the lowest. The results show that the proposed method outperforms the conventional UFLS by 7.31% in terms of improved ENS.